Screening of cognitive impairment in patients with Parkinson's disease: diagnostic validity of the Brazilian versions of the Montreal Cognitive Assessment and the Addenbrooke's Cognitive Examination-Revised - Emmanuelle Sobreira; Márcio A. Pena-Pereira; Alan L. Eckeli; Manoel A. Sobreira-Neto; Marcos H. N. Chagas; Maria P. Foss; Brenna Cholerton; Cyrus P. Zabetian; Ignacio F. Mata; Vitor Tumas (Arquivos de Neuro-Psiquiatria)
ABSTRACTObjective The aim of the present study is to examine the accuracy of the Brazilian versions of the Montreal Cognitive Assessment (MoCA) and the Addenbrooke's Cognitive Examination-Revised (ACE-R) to screen for mild cognitive impairment (PDMCI) and dementia (PDD) in patients with Parkinson's disease (PD).Method Both scales were administered to a final convenience sample of 79 patients with PD. Patients were evaluated by a neurologist, a psychiatrist and a neuropsychologist using UPDRS, Hoehn and Yahr and Schwab and England scales, global deterioration scale, a psychiatric structured interview, Mattis Dementia Rating Scale and other cognitive tests.Results There were 32 patients with PDMCI and 17 patients with PDD. The MoCA and the ACE-R were able to discriminate patients with PDD from the others.Conclusion Both scales showed to be useful to screen for dementia but not for mild cognitive impairment in patients with PD.